Regional Financial Development and Firm Growth in Peru - Eduardo Moron; Edgar Salgado; Cristhian Seminario (Inter-American Development Bank (IDB), 2013)
This paper documents the relationship between regional financial development and firm growth in the Peruvian manufacturing sector. In order to control for mutual causality between credit availability and firm growth, industry differences in financial dependence on external funds are exploited. The 1994 and 2008 rounds of the National Economic Census are used, permitting analysis at the firm level as well as the activity level. Results suggest a significant and positive effect of financial deepening on surviving firms` growth. However, this effect is smaller for micro enterprises, suggesting that the cost of external funding decreases with financial development mainly for large firms. The conclusions remain unchanged when entering and exiting firms are included. The paper further finds that credit expansion have encouraged not only firm growth but also firm entry. The results are robust using an alternative measure of financial dependence.
Keywords: D22; D53; G21; L11; L60; O14; 330